PENINGKATAN KEMAMPUAN MENULIS KARANGAN SISWA KELAS IV SD MENGGUNAKAN MEDIA GAMBAR BERSERI - Fitriani, Wihelmina; Mutiarawati, Ira; Sausan, Inas (Prosiding Temu Ilmiah Nasional Guru, 2023)
The problem in writing ability of indonesian subject is the lack of interest dan motivation to learn. Based on these problems, this Classroom Action Research (CAR) aimed to improve the skills of writing simple essay by using serial images that is displayed through a projector in class IV SD Kandawati II class with a total of 29 student. Data were collected using post test and observation. The result showed that average score of post test in cycle I is 66.72, then in cycle II increased significantly to 97.58. The score of classical completeness in cycle I is 31%, where only 9 students had complete. Then in cycle II, the classical completeness also increased to 96%, only 1 student had not completed. The results of observations showed that student’s participation is increase from 62.50% (cycle I) to 82.50% (cycle II). So using serial images media in Bahasa Indonesia subject can improve student’s ability in writing simple essays for elementary students in class IV SDN Kandawati II.